Clinical value of alpha-fetoprotein in the detection of mammary carcinoma in female dogs - Senhorello, I. L. S. [UNESP]; Terra, E. M.; Sueiro, F. A. R.; Pereira, R. S.; Firmo, B. F. [UNESP]; Martinelli, C.; Tinucci-Costa, M. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
This study aimed to assess the behavior of Alpha-Fetoprotein (AFP) in healthy female dogs, those with non-metastatic mammary carcinomas, and those with metastatic mammary carcinomas. Additionally, it aimed to evaluate serum levels concerning the clinical-pathological variables of diseased dogs. To achieve this, sera from 35 female dogs were utilized, divided into three groups: G1 (n=10), control group (dogs free of neoplasms); G2 (n=20), dogs with mammary carcinoma without lymph node metastasis; and G3 (n=5), dogs with mammary carcinoma with lymph node metastasis. AFP was measured through ELISA, and the results were assessed using the Tukey test with a significance level of 5% in terms of the marker's presence in the patient's serum, its relationship with the neoplasm's biological behavior, and the clinical-pathological alterations encountered. Additionally, sensitivity and specificity values were obtained to establish the clinical value of AFP as a serological marker. The results revealed that AFP values (p<0.001) were significantly higher in dogs with mammary carcinoma compared to healthy dogs. Furthermore, there was a significant increase in AFP in non-spayed animals (p=0.0307). The marker demonstrated a sensitivity of 92% and specificity of 90% in distinguishing diseased animals from healthy ones. No relationship was found between the variables of tumor size, lymph node metastasis, histological grade, necrosis, ulceration, and inflammation with AFP (p<0.05). The findings indicated that AFP is elevated in female dogs with mammary tumors and could be a promising marker for monitoring dogs with mammary neoplasms. Future studies that include patient follow-up will be necessary.
Keywords: prognosis; mammary tumor; biomarkers; metastasis